Koherensi Dalil Naqli: Pendapat Imam Mazhab dan Astronomi dalam Pemaknaan Fajar - Qomariyah, Nur; Maulidia, Rinata; Ihsani, Ma’dinal; Agustina, Indi Rizky Amalia; Qulub, Siti Tatmainul; Rohman, Holilur (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
The issue of dawn is a classic discussion that is interesting to study. Rumors about the differences in interpretation of the Sharia evidence from the perspective of the imam of the school of thought and astronomy have become an actual discussion that is never-ending to be reviewed. It seems that dawn is one of the determinants of the entry of the five obligatory prayer times, so it is an urgent problem among Muslims to know the form of visualization and when dawn occurs. Therefore, it is necessary to have a match between the naqli evidence and the opinions of the imam of the school of thought and astronomy to interpret dawn as a sign of the entry of the morning prayer time. However, if there is a discrepancy between the three, it does not necessarily mean that the sharia evidence needs to be corrected. But rather an oversight in interpreting and studying nature regarding its relationship to the sharia evidence.